Adventitial cystic disease of the common femoral artery - Abdalla A. Butt; Farhad R. Udwadia; Gautamn Sarwal; D. Kirk Lawlor (Annals of Vascular Surgery - Brief Reports and Innovations, 2022)
Adventitial Cystic Disease (ACD) is a rare cause of peripheral arterial disease that accounts for less than 1% of all causes of claudication. It typically presents in younger individuals and surgical reconstruction is the mainstay of treatment. We report a case of a 60-year-old, active female with progressively worsening claudication, who presented with ultrasound and computed tomography angiography revealing ACD involving the common femoral artery. The patient underwent a complete resection of the affected artery, which was replaced with an interposition Dacron bypass graft. We also present a comprehensive review of literature on surgical management of ACD of the femoral artery.